PENGARUH KELEMBABAN TANAH TERHADAP LAJU INFEKSI JAMUR Phytium sp Dan Rhizoctonia sp PENYEBAB PENYAKIT BLAS PADA PEMBIBITAN PRE NURSERY KELAPA SAWIT (Elaeis guineensis Jacq) - Harry Sujadmiko (AGRIUM: Jurnal Ilmu Pertanian, 2012)
AbstractStudies have been conducted to determine the effect of soil moisture on the rate of fungal infection Phytium sp and Rhizoctonia sp in pre nursery seedlings of oil palm, Elaeis guineensis Jacq use Randomized Design Group non-factorial, consisting of 6 treatments with 3 replications. The results showed: blast disease is a disease that is not important because it can only cause disease by 25% or 9 plants of the total sample of 36 plants. Soil moisture content of 10% good to blast disease attack, in addition to 25% soil moisture conditions are good also for blast disease attack. Humidity above 50% unfavorable conditions for blast disease attack. Symptoms caused by fungal attack and Rhizoctonia sp sp Phytium leaves change color from brownish green color and spreads throughout the leaf surface and there is a bright yellow color with brown patches of dead tissue.Keywords: humidity, the rate of infection, Phytium sp, Rhizoctonia sp, palm oil